2009
DOI: 10.1172/jci37948
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid action induces autophagy-mediated cell death through stimulation of ER stress in human glioma cells

Abstract: Autophagy can promote cell survival or cell death, but the molecular basis underlying its dual role in cancer remains obscure. Here we demonstrate that Δ 9 -tetrahydrocannabinol (THC), the main active component of marijuana, induces human glioma cell death through stimulation of autophagy. Our data indicate that THC induced ceramide accumulation and eukaryotic translation initiation factor 2α (eIF2α) phosphorylation and thereby activated an ER stress response that promoted autophagy via tribbles homolog 3-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
601
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(632 citation statements)
references
References 37 publications
26
601
3
2
Order By: Relevance
“…As ER stress-induced upregulation of TRB3 induces autophagy and the inhibition of the Akt/mTORC1 axis, 41 we investigated the contribution of TRB3 to BRAF V600E -induced basal autophagy. RNAi-mediated knockdown of TRB3 was carried out in A375 cells (Figure 6c) and the effect on basal autophagy rate analysed in the presence or absence of bafilomycin.…”
Section: Resultsmentioning
confidence: 99%
“…As ER stress-induced upregulation of TRB3 induces autophagy and the inhibition of the Akt/mTORC1 axis, 41 we investigated the contribution of TRB3 to BRAF V600E -induced basal autophagy. RNAi-mediated knockdown of TRB3 was carried out in A375 cells (Figure 6c) and the effect on basal autophagy rate analysed in the presence or absence of bafilomycin.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this observation and with the notion that TRIB3 participates in the regulation of AKT phosphorylation by mTORC2, we found that genetic inactivation of TRIB3 leads to an enhanced phosphorylation of FOXO and BAD but not of GSK3or PRAS 40. Moreover, we recently found that treatment with D 9 -tetrahydrocannabinol (a compound derived from the plant Cannabis sativa that exerts antitumor effects in mouse models of cancer 14,15,35 ) triggers AKT inhibition via an enhanced interaction of TRIB3 with AKT and a subsequent decrease in the interaction of AKT and TRIB3 with the mTORC2 complex. 19 Our data also show that Trib3 interacts more strongly with WT AKT, or with AKT mutants in which Thr 308 and Ser 473 have been mutated to Ala, than with AKT mutants in which these two phosphorylatable residues have been mutated to Asp to mimic the negative charge associated with their phosphorylation (author's unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In addition, administration of different anticancer agents promotes cancer cell death via TRIB3 upregulation and the subsequent inhibition of Akt. [13][14][15][16][17][18][19] However, the precise molecular basis of the regulation of Akt by TRIB3 and whether loss of this pseudokinase may contribute to cancer initiation and progression remains to be clarified.In this study, we investigated the effect of the genetic inactivation of TRIB3 in several cellular and animal models of cancer. Our findings indicate that genetic inhibition of TRIB3 enhances tumorigenesis and that this effect is due -at least primarily -to a selective inactivation of the transcription factor FOXO by the mammalian target of rapamycin complex 2 (mTORC2)/AKT axis.…”
mentioning
confidence: 99%
“…While knockdown suppresses the effect of GMCSF withdrawal, overexpression of Trib2 stimulates apoptosis by means of a caspase, not the proteosome (Lin et al, 2007). Trib3 also promotes apoptosis in macrophages (Shang et al, 2009), gliomas (Salazar et al, 2009), pancreatic b-cells (Humphrey et al, 2010), and chondrocytes (Cravero et al, 2009). …”
Section: Tribs Promote Apoptosismentioning
confidence: 99%